Observations on the decadal variability of aerosol in eastern Himalayan foothills: Evidence of an anthropologically induced positive shift. (15th April 2023) - Subba, Tamanna; Pathak, Binita; Gogoi, Mukunda M.; Ajay, P.; Dahutia, Papori; Chakraborty, Aniket; Bhuyan, Pradip K.
Abstract: The decadal variability of direct radiative effects of aerosols is investigated at Dibrugarh, a site in northeast India (NEI) at the eastern Himalayan foothills, primarily using multi-wavelength solar radiometer measurements spanning from October 2001 to February 2020. The ground-based aerosol observations are combined with satellite remote sensing, reanalysis data, and model simulations to study the change in atmospheric particle loading over the region. Observations indicate a statistically significant increase (∼0.015 yr −1 ) in Aerosol Optical Depth (AOD) during the last two decades in line with an increase in human activity. As compared to 2001–2007 (we call it as Stage I), the aerosol burden has grown rapidly during 2008 until 2020 (Stage II). AOD at 500 nm is found to increase by ∼40% from Stage I to Stage II, resulting in an increase in the aerosol direct radiative forcing (DRF) at the top of the atmosphere (TOA) by ∼43% during stage II (∼−16.0 W m -2 ), from the base value of −11.2 W m −2 in Stage I. Decreasing biomass burning activities, black carbon aerosol mass concentration, and high sulfate and organic aerosols are the primary factors responsible for the trend in TOA cooling by −0.46 W m −2 yr −1 . This is further aided by the decrease in rainfall over NEI. MERRA-2 data analysis shows a similar enhancements in aerosol load over the entire NEI and the adjacent highly polluted Indo-Gangetic Plains (IGP). A similar feature is seen over the IGP, primarily driven by anthropogenic emissions, but precedes that in NEI by about a year. A simulation of the regional climate model (RegCM) over the south Asian domain quantifies the contribution of aerosol loading over NEI due to the aerosols carried from the IGP. In the highest aerosol loading period, about 12–30% of the aerosols, equivalent to 15–30% of atmospheric warming, are transported from the IGP to the NEI. Graphical abstract: Image 1 Highlights: AOD and direct radiative forcing show a two-stage pattern, transitioning from low to high values over NEI. The transition from low to high aerosol loading was similar in the IGP region. Decreasing biomass burning, BC aerosols, and increasing sulfate and organic aerosols contribute to elevated TOA cooling. Based on RegCM4.4 simulations, IGP transports 12–30% of aerosols over NEI.